Indikator Keuangan dan Non-Keuangan melalui ROI yang Diterapkan dalam Sosial Media Marketing - Iwan Darmawansyah; Sismiati Sismiati (JUDICIOUS, 2021)
This study aims to develop instruments that marketers can use in developing digital marketing in their industry. The method used is applied research and constructivism point of view. Researchers conducted interviews and developed digital marketing strategies. The results of this study explain that call to action provides consumer effectiveness in purchasing products. However, it is necessary to encourage promotion through ig paid to provide a wider range of promotions. This study also explains some important things to consider in preparing the target market by analyzing customer personals and designing customer journeys.